2007
DOI: 10.1002/pc.20347
|View full text |Cite
|
Sign up to set email alerts
|

Composite screen‐printed thick films for high dielectric constant devices: Bi4Ti3O12–CaCu3Ti4O12 films

Abstract: In this paper, we did a study of the effect of the presence of BIT (Bi4Ti3O12) in the dielectric and optical properties of the CaCu3Ti4O12 (CCTO) thick films. The films were prepared by the solid sate procedure. Mechanical alloying followed by the solid state procedure has been used successfully to produce powders of CaCu3Ti4O12 (CCTO) and BIT (Bi4Ti3O12) to be used in the composites. We also look at the effect of the grain size of the BIT and CCTO in the final properties of the composite film. The samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Electronic ceramics [6][7][8][9] have many applications in microwave communication systems [10][11][12], where dielectrics are used both for elements in microwave integrated circuits and for the substrates on which circuit elements are fabricated. The ferrites are a group of electronic ceramics, which are used in microwave components like circulators and isolators.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic ceramics [6][7][8][9] have many applications in microwave communication systems [10][11][12], where dielectrics are used both for elements in microwave integrated circuits and for the substrates on which circuit elements are fabricated. The ferrites are a group of electronic ceramics, which are used in microwave components like circulators and isolators.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that the infrared optical reflectivity measurements and numerical analysis can be used to obtain reliable information on whether the ceramic has a cubic or tetragonal unit cell. Since the emittance is dependent on its crystal structure and mineralogical composition [21,22], we investigated the crystal structure and the chemical composition of the powders. The mineralogical analysis of the FIR ceramic powders by XRF presented in our previous article showed that the FIR ceramic powders consisted of five major elements (O, Na, Al, K, and Si) and seven minor elements (Ca, S, Cl, P, Ti, Fe, and Ba) [23]; these elements had high far-infrared radioactivity [24].…”
Section: Resultsmentioning
confidence: 99%
“…The angle of tilt is sufficiently large such that the Cu 2+ ions occupy an essentially square‐planer environment. Subramanian and coworkers proposed that cubic perovskite, CaCu 3 Ti 4 O 12 , has a high dielectric constant of approximately 10 4 at room temperature, which exhibits an extraordinarily high and relatively temperature‐independent dielectric constant in a wide temperature range of 100–400 K . Its structure does not change down to 35 K. High dielectric constant has been attributed to barrier layer formation at grain boundaries or due to formation of twin boundaries during the sintering process , which gives rise to a barrier layer capacitor structure leading to very high dielectric constant.…”
Section: Introductionmentioning
confidence: 99%